Use of technology in University: education bibliometric exploration - Navarro-Castillo, Yulissa (2024)
The aim of this article is to scrutinize the advancement and significance of technology utilization in higher education, with the purpose of comprehending present trends and identifying novel avenues of inquiry that are of significance to the academic community. A quantitative approach was employed by conducting a bibliometric analysis on 43 scientific articles retrieved from the Scopus database, in order to obtain the most pertinent metrics of high-impact publications that were produced up until 2023. The research findings regarding the implementation and use of technology at the university level are very dispersed and underdeveloped, with the most relevant topics being motivation and the human factor in learning with technologies. Furthermore, a concentration of articles was found in four countries and in 31% of scientific journals. This study is unique because it applies a methodology enhanced with the use of a digital tool for a level that is underserved in terms of research and education at the university level.